E-MODULE DEVELOPMENT COMPUTER BASED ACCOUNTING WORK-BASED LEARNING (WBL) - Hendri Gunawan; Heri Pratikto; Madziatul Churiyah (Transpublika Publisher, 2023)
The utilization of a computer-based approach offers numerous advantages for work-based learning in the field of accounting. This approach enables students to simulate intricate accounting tasks and scenarios using specialized software applications, thus furnishing them with a lifelike environment to cultivate practical skills. The electronic module (e-module) encompasses a range of interactive exercises, case studies, and simulations meticulously designed to replicate genuine workplace situations. This research aims to develop an effective computer-based work-based learning (WBL) accounting e-module that enhances students' practical skills and their ability to apply accounting knowledge in real-world scenarios. The research followed a research and development approach, utilizing the Rowntree development model. Formative evaluation was conducted based on Tessmer & Martin's theory. The study consisted of stages including analysis of teaching materials, tailored e-module development, prototype creation (paper-based and computer-based), expert evaluation, and field testing. The developed accounting e-module successfully simulates real workplace situations through interactive exercises, case studies, and simulations. Expert evaluation confirmed the suitability of the learning media. Field testing, encompassing various settings, revealed increased student engagement, motivation, and improved learning outcomes. This research led to the creation of a robust work-based learning (WBL) accounting computer e-module. The module effectively bridges theoretical learning with practical application, enhancing students' skills and performance in the field of accounting. The findings affirm the viability and effectiveness of the developed e-module as a valuable pedagogical tool.